Prevalence of Naturally-Occurring NS5A and NS5B Resistance-Associated Substitutions in Iranian Patients With Chronic Hepatitis C Infection - Rahimi, Pooneh; Sharafi, Heidar; Bahramali, Golnaz; SajadianFard, FaridehSadat; Asadi, Nafiseh Sadat; Alavian, Seyed Moayed; Iranpur Mobarakeh, Vahid; Moravej, Seyedeh Zahra (Frontiers in Microbiology, 2021)
Background: Hepatitis C virus (HCV) non-structural 5A (NS5A) and non-structural 5B (NS5B) resistance-associated substitutions (RASs) are the main causes of failure to direct-acting antiviral agents (DAAs). NS5A and NS5B RASs can occur in patients with HCV infection naturally and before exposure to DAAs. Objectives: This study aimed to evaluate naturally-occurring NS5A and NS5B RASs in Iranian patients with HCV genotype 1a (HCV-1a) and -3a infections. Methods: In this cross-sectional study, viral RNA was extracted from serum specimens. NS5A and NS5B regions were amplified using RT-PCR followed by DNA sequencing. The results of nucleotide sequences were aligned against reference sequences of HCV-1a and -3a and the amino acid substitutions were analyzed using geno2pheno [hcv] web application. Results: Among 135 patients with hepatitis C, NS5A amino acid substitutions/RASs were identified in 26.4% and 15.9% of patients with HCV-1a and -3a infections, respectively. The identified amino acid substitutions/RASs in the NS5A region of patients with HCV-1a infection were M28T/V/I 11.11%, Q30R/H 4.16%, L31M 1.38%, and H58Y/P/C/D/Q 16.67%. Y93H substitution was not found in HCV-1a sequences. In patients with HCV-3a infection, NS5A amino acid substitutions/RASs were A30K/R/T 9.52%, L31F 1.58%, P58S/T/C 3.17%, Y93H 3.17%, and Y93N 3.17%. No resistance substitutions were identified in NS5B sequences from patients with HCV-1a and -3a infections. Conclusions: In this study, baseline amino acid substitutions/RASs were only identified in the NS5A region in Iranian patients with HCV-1a and -3a infections, and the rate of these amino acid substitutions/RASs were in accordance with similar studies. There were no RASs in the HCV-1a and -3a NS5B region.